2009
DOI: 10.1080/08916930903039810
|View full text |Cite
|
Sign up to set email alerts
|

Sera of patients with systemic lupus erythematosus react with plasmodial antigens and can inhibit thein vitrogrowth ofPlasmodium falciparum

Abstract: The acquisition of protective immunity in malaria is a slow process during which autoantibodies are produced. The present work aimed at studying a possible interference of autoimmune responses on malaria immune protection. This was done by investigating the presence of autoantibodies in the sera of malarious patients, by searching for reactivity of autoantibodies from autoimmune patients against plasmodial antigens, and by studying the effect of such antibodies on the in vitro growth of Plasmodium falciparum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
(54 reference statements)
0
21
0
Order By: Relevance
“…As previous works used only purified IgG preparations (Singh et al 2001, Zanini et al 2009), the present study is the first to show that monoclonal auto-Ab can inhibit in vitro P. falciparum growth. �his result was expected, because monoclonal antibody crossreactions between plasmodial and mammalian cells were reported more than two decades ago (Daniel-Ribeiro et al 1984b, Li et al 1995, Crandall et al 1996.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…As previous works used only purified IgG preparations (Singh et al 2001, Zanini et al 2009), the present study is the first to show that monoclonal auto-Ab can inhibit in vitro P. falciparum growth. �his result was expected, because monoclonal antibody crossreactions between plasmodial and mammalian cells were reported more than two decades ago (Daniel-Ribeiro et al 1984b, Li et al 1995, Crandall et al 1996.…”
Section: Discussionmentioning
confidence: 92%
“…However, the strongest evidence supporting the protective role of autoimmunity in plasmodial infection has been provided by two independent studies, which showed that sera and IgG antibodies from SLE patients can react with and inhibit the in vitro growth of P. falciparum (Singh et al 2001, Zanini et al 2009). �he present paper expands these findings by showing that sera from patients with other AID, containing auto-Ab of different specificities, can also react against P. falciparum and inhibit the parasite's in vitro growth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations